Transformasi Evaluasi Kinerja Karyawan Berbasis Electronic Human Resource Management (E-HRM) dalam Meningkatkan Efektivitas Manajemen Sumber Daya Manusia pada Era Industry 4.0 - Fazrin Muchtar; Zakky Zamrudi; Syahrial Shaddiq (INDO PUBLISHING, 2025)
This study aims to analyze the transformation of employee performance evaluation based on Electronic Human Resource Management (e-HRM) in improving the effectiveness of human resource management in the Industry 4.0 era. The research method uses a qualitative approach with a case study design through in-depth interviews, observations, and analysis of documents related to the implementation of e-HRM in the performance appraisal process. The results show that the digitization of performance evaluation through e-HRM can improve the accuracy of assessments, strengthen transparency, accelerate the evaluation process, and enable real-time performance monitoring that supports data-driven decision making. The discussion reveals that e-HRM has a positive impact on increasing productivity and the effectiveness of HR management, but its implementation still faces obstacles such as variations in employee digital literacy, work culture resistance, and the need for more comprehensive system integration. The research conclusion emphasizes that e-HRM-based performance evaluation transformation is an important strategy for strengthening the effectiveness of human resource management and increasing organizational competitiveness in facing the demands of Industry 4.0.